Sikap, Aspirasi dan Kemampuan Wirausaha: Dimensi Utama Kinerja Kewirausahaan - Prasetyo, P Eko (Jurnal Manajemen dan Kewirausahaan, 2020)
The purpose of this study is to analyze the effect of attitudes, aspirations and abilities of entrepreneurs towards the success of entrepreneurial performance. The main data source in this study used 2019 global entrepreneurship index data (GEINDEX) from 137 countries. The analytical method uses the path analysis model. The research results show there are three main factors that are most fundamental in achieving successful entrepreneurial performance, namely risk acceptance factors, internationalization aspirational factors, and the ability to absorb technology. In other words, the main basic capital to achieve successful entrepreneurial performance in the era of globalization: 1) must accept existing risks, 2) has the global thought aspirations (internationalization), and 3) Â have the capacity to absorb existing technology. However, the first key to success in achieving entrepreneurial performance is very much dependent on the strength of the aspirations or big dreams possessed by an entrepreneur.https://doi.org/10.26905/jmdk.v8i2.4174